New records of the genus Nola Leach, 1815 (Lepidoptera, Nolidae, Nolinae) from China, with description of a new species - Chen, Zhe-Jing; Zhang, Bei-Bei; Hu, Yan-Qing (Zootaxa, 2022)
The new species, Nola nayongensis sp. nov., is described from Guizhou, China. Nola canioralis (Walker, 1863) is reported from China for the first time. Nola quadriguttula Inoue, 2000 and Nola thyrophora (Hampson, 1914) are reported from mainland China for the first time. The distributions of three known species from China (Nola pseudendotherma László, Ronkay & Ronkay, 2014, Nola duplicilinea (Hampson, 1900) and Nola astigma Hampson, 1894) are updated. Adults and the male genitalia are illustrated.